Macroscopic tumor dimension, sentinel lymph node outcome, and survival analysis among cutaneous melanoma - Asato, Marcel A. [UNESP]; Moraes-Neto, Francisco A.; Moraes, Marcelo Padovani de Toledo [UNESP]; Ocanha-Xavier, Juliana P. [UNESP]; Alencar Marques, Mariangela Esther [UNESP]; Xavier-Junior, Jose Candido C. [UNESP] (Wiley, 2024)
Background: Cutaneous melanoma is characterized by a high risk of metastasis to distant organs and a substantial mortality rate. For planning treatment and assessing outcomes, the Breslow micrometric measurement is critical. The tumor macroscopic dimension is not considered a prognostic parameter in cutaneous melanoma, although there are studies showing that tumor size is an independent prognostic factor for melanoma-specific survival. Therefore, this study aimed to evaluate the macroscopic dimension of melanoma and other known prognostic factors (i.e., Breslow index, mitoses, regression, and ulceration) as predictors of sentinel lymph node outcome and survival outcome. Methods: We performed a retrospective cross-sectional study of 227 melanoma lesions subjected to sentinel lymph node biopsy at two Brazilian referral centers. Results: On univariate analysis, there was a statistically significant correlation between the largest macroscopic tumor dimension and the sentinel lymph node result (P = 0.001); however, on multivariate analysis considering all evaluated parameters, there was no significant difference between the sentinel lymph node result and the tumor macroscopic dimension (P = 0.2689). Regarding melanoma-specific survival, the macroscopic dimension showed no significant correlation (P = 0.4632) in contrast to Breslow's dimension (P < 0.0001). Conclusion: The Breslow thickness was the only significant factor related to both the sentinel lymph node outcome and melanoma specific survival among the evaluated variables.